Eurosensors 2018 2018
DOI: 10.3390/proceedings2130897
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modifications in Free-Standing InGaN/GaN LEDs after Femtosecond Laser Lift-Off

Abstract: A laser lift-off (LLO) process has been developed for detaching thin InGaN/GaN lightemitting diodes (LED) from their original sapphire substrates by applying an ultrafast laser. LLO is usually based on intense UV irradiation, which is transmitted through the sapphire substrate and subsequently absorbed at the interface to the epitaxially grown GaN stack. Here, we present a successful implementation of a two-step LLO process with 350 fs short pulses in the green spectral range (520 nm) based on a two-photon abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Although the InGaN/ GaN MQW layers were still in a good condition (i.e., no significant defect was shown), a damage still appeared within the n-GaN layer, which is at ∼2 μm from the fs-LLO-released interface. This result is similar to those obtained in other previously reported LLO cases, 33,68,69 in which the location of structural defects or damages depends on the used laser pulse width and its absorption coefficient of GaN. One of the studies related to structural damages occurring in LLO processes has demonstrated that a laser possessing a higher absorption coefficient of GaN will yield shallower penetration depth (e.g., a 248 nm KrF excimer laser with a pulse time of 35 ns).…”
Section: Resultssupporting
confidence: 90%
“…Although the InGaN/ GaN MQW layers were still in a good condition (i.e., no significant defect was shown), a damage still appeared within the n-GaN layer, which is at ∼2 μm from the fs-LLO-released interface. This result is similar to those obtained in other previously reported LLO cases, 33,68,69 in which the location of structural defects or damages depends on the used laser pulse width and its absorption coefficient of GaN. One of the studies related to structural damages occurring in LLO processes has demonstrated that a laser possessing a higher absorption coefficient of GaN will yield shallower penetration depth (e.g., a 248 nm KrF excimer laser with a pulse time of 35 ns).…”
Section: Resultssupporting
confidence: 90%
“…Laser processing is at the forefront of technology in the display industry; lasers enable mass production of the most demanding tasks [4]. They enable the cutting of substrates, fine patterning, low-temperature polycrystalline silicon (LTPS) annealing [5], temporary carrier delamination (laser lift-off) for flexible displays [6], and more. Laser processing offers several opportunities for MicroLED display production:…”
Section: Laser Applications In Microled Manufacturingmentioning
confidence: 99%